2017
DOI: 10.1007/s00066-017-1213-y
|View full text |Cite|
|
Sign up to set email alerts
|

Left-sided breast cancer and risks of secondary lung cancer and ischemic heart disease

Abstract: The results indicate that 3D-CRT plans in DIBH pose the lowest risk for both major coronary events and secondary lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 63 publications
2
54
0
Order By: Relevance
“…Even though clinicians have to give particular attention to these complications, anthracycline treatment [60][61][62]) is an additional major risk factor for additional cardiotoxicity during radiotherapy with a synergistic effect. However, the use of anthracycline, other cardiotoxic chemotherapies, immunotherapy [63][64][65] and targeted therapies [66,67] should only be used with great caution and only after carrying out a careful treatment plan and optimization [1,30,40]. There is a wealth of evidence from retrospective and planning studies demonstrating reduction in dose to the heart and coronary arteries with DIBH treatment of left-sided breast cancers [10,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though clinicians have to give particular attention to these complications, anthracycline treatment [60][61][62]) is an additional major risk factor for additional cardiotoxicity during radiotherapy with a synergistic effect. However, the use of anthracycline, other cardiotoxic chemotherapies, immunotherapy [63][64][65] and targeted therapies [66,67] should only be used with great caution and only after carrying out a careful treatment plan and optimization [1,30,40]. There is a wealth of evidence from retrospective and planning studies demonstrating reduction in dose to the heart and coronary arteries with DIBH treatment of left-sided breast cancers [10,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Darby et al [16] found after retrospectively analyzing 2168 patients from the Nordic cancer registry that the relative risk for ischemic heart disease increased by 7.4 % for every 1 Gray (Gy) in mean heart dose. However especially the Ramus interventricularis anterior (RIVA; left anterior descending coronary artery-LAD-CA) has a high risk of obtaining significant higher doses and is responsible for the development of pathologic blood vessel disorder and myocardial or coronary artery disease [1,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation oncologists implement several methods to decrease IR dose to the heart for minimizing the risk of RACVD (76), such as prone positioning (77), heart block with electronic compensation (57), heart-sparing three-dimensional printing technique (78), continuous positive airway pressure (CPAP) (79), real-time position management (RPM) inspiration gating (80,81), proton-beam irradiation (82)(83)(84)(85), and deep-inspiration breath-hold technique (DIBH) (86)(87)(88)(89)(90). However, even with the highly recommended visual-guided DIBH technique, residual variations of the heart position are still noticeable (91).…”
Section: Clinical Challenges Of Decreasing the Risk Of Racvd In Modermentioning
confidence: 99%
“…Recent data show that even low radiation doses to the heart can play a relevant role in the development of late cardiac toxicity after BC treatment [51,52]. However, neither the exact pathomechanisms nor the exact dose-response relationships or the critical regions within the heart are well defined.…”
Section: Role Of Modern Techniques: Imrt Vmat and Dibhmentioning
confidence: 99%